Karp's Theorem in Inverse Obstacle Scattering Problems (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this work, we provide a proof of the so-called Karp's theorem in a different approach. We use the unique continuation principle together with the monotonicity of eigenvalues for the negative Laplace operator. This method is new and would be applicable to other types of inverse scattering problems.